Improvement in Stroke Risk Prediction: Role of C-Reactive Protein and Lipoprotein-Associated Phospholipase A2 in the Women's Health Initiative. Issue 7 (October 2014) - Wassertheil-Smoller, Sylvia; McGinn, Aileen; Allison, Matthew; Ca, Tianxi; Curb, David; Eaton, Charles; Hendrix, Susan; Kaplan, Robert; Ko, Marcia; Martin, Lisa W.; Xue, Xiaonan
Background: Classification of risk of ischemic stroke is important for medical care and public health reasons. Whether addition of biomarkers adds to predictive power of the Framingham Stroke Risk or other traditional risk factors has not been studied in older women. Methods: The Hormones and Biomarkers Predicting Stroke Study is a case-control study of blood biomarkers assayed in 972 ischemic stroke cases and 972 controls, nested in the Women's Health Initiative Observational Study of 93 676 postmenopausal women followed for an average of eight-years. We evaluated additive predictive value of two commercially available biomarkers: C-reactive protein and lipoprotein-associated phospholipase A2 to determine if they added to risk prediction by the Framingham Stroke Risk Score or by traditional risk factors, which included lipids and other variables not included in the Framingham Stroke Risk Score. As measures of additive predictive value, we used the C-statistic, net reclassification improvement, category-less net reclassification improvement, and integrated discrimination improvement index. Results: Addition of C-reactive protein to Framingham risk models or additional traditional risk factors overall modestly improved prediction of ischemic stroke and resulted in overall net reclassification improvement of 6·3%, (case net reclassification improvement = 3·9%, control net reclassification improvement = 2·4%). In particular, high-sensitivity C-reactive protein was useful in prediction of cardioembolic strokes (net reclassification improvement = 12·0%; 95% confidence interval 4·3–19·6%) and in strokes occurring in less than three-years (net reclassification improvement = 7·9%, 95% confidence interval 0·8–14·9%). Lipoprotein-associated phospholipase A2 was useful in risk prediction of large artery strokes (net reclassification improvement = 19·8%, 95% confidence interval 7·4–32·1%) and in early strokes (net reclassification improvement = 5·8%, 95% confidence interval 0·4–11·2%). Conclusions: C-reactive protein and lipoprotein-associated phospholipase A2 can improve prediction of certain subtypes of ischemic stroke in older women, over the Framingham stroke risk model and traditional risk factors, and may help to guide surveillance and treatment of women at risk.